An exploration of how selective mutism training informs teachers' understanding and practice. Issue 1 (18th February 2022) - White, Joe; Bond, Caroline; Carroll, Claire
Abstract : This small‐scale research project explored the perceived impact which selective mutism (SM) training, delivered by an educational psychologist (EP), had on school practitioners' understanding of the condition and their subsequent professional practice. Three teachers were interviewed and a thematic analysis elicited four superordinate themes. Participants recognised that they had little previous knowledge of SM and many misconceptions; they also identified key ways in which their understanding of SM, and their practice as school professionals, had developed. In addition, staff highlighted central challenges which nevertheless remained, one of which involved working with parents. This research highlights the limited knowledge which teachers have of SM, whilst demonstrating how staff training and school development might contribute to improved outcomes for children with the condition. Implications for teacher training programmes and future research are considered.